Lactic Acid Bacteria in Fermented Foods of Indonesian Origin - Endang Sri Rahayu (agriTECH, 2003)
In this study, about 194 lactic acid bacteria strains have been isolated from 21 kinds of fermented foods (plant materials and fish origin). These fermented foods were salted-fermented fruits, vegetables & fish; fermented raw cassava (gatot & growol); tape (cassava & glutinous rice); microbial starter cultures (ragi); and fermented soybean (tempe & moromi). Among these strains, 109 belong to genus Lactobacillus, which dominated by homofermentative Lactobacillus plantarum pentosus, 25 strains belong to Pediococcus (mostly P. pentosaceus acidilactici), 45 strains Streptococcus which mostly identified as Streptococcus thermophilus, 7 strains belong to Enterococcus, which further identified as E. faecium and 8 strains Leuconostos (Weisella) as Weisella paramesenteroides. Lactobacilli have been found in all fermented foods, pediococci in 11 kind of fermented foods both plant material and fish origin, while streptococci mostly found in fermented fish, as well as enterococci and Leuconostoc. Nine strains belong to Lactobacillus plantarum - pentosus complex from different fermented food samples have been determined their DNA-DNA homology to L. plantarum NRIC 1067 and L. pentosus NRIC 1069. Result of their homology to these strains shown that all these nine strains are identified as L. plantarum. Lactic acid bacteria from Indonesian fermented foods are dominated by Lactobacillus plantarum, followed by Pediococcus pentosaceus, and Streptococcus thermophilus.